N-Acetylcysteine attenuates lipopolysaccharide-induced apoptotic liver damage in D-galactosamine-sensitized mice - Wang Hua; Xu De-xiang; Lu Jin-wei; Zhao Lei; Zhang Cheng; Wei Wei (Acta Pharmacologica Sinica, 2016)
Aim: To investigate the effects of N-acetylcysteine on D-galactosamine (GalN)/lipopolysaccharide (LPS)-induced apoptotic liver injury in mice. Methods: When given together with a low dose of LPS, GalN highly sensitizes animals to produce apoptotic liver injury with severe hepatic congestion, resulting in rapid death. In the GalN/LPS model, TNF-α is the major mediator leading to apoptotic liver injury. Reactive oxygen species (ROS) are involved in GalN-induced sensitization to TNF-α-evoked hepatocyte apoptosis. N-acetylcysteine (NAC) is an antioxidant and a glutathione (GSH) precursor. In this study, we investigated the effects of NAC on LPS-induced apoptotic liver injury in GalN-sensitized mice. Results: Pretreatment with NAC significantly reduced GalN/LPS-induced elevation of serum alanine aminotransferase levels. In parallel, GalN/LPS-induced hepatic necrosis and congestion were obviously improved by NAC. Furthermore, NAC pretreatment significantly alleviated GalN/LPS-induced hepatic apoptosis, measured by the inhibition of hepatic caspase-3 activity and attenuation of DNA laddering. NAC pretreatment had no effect on LPS-evoked nitric oxide production in GalN-sensitized mice. Increases in serum TNF-α concentration, which were observed in GalN/LPS-treated mice, were not significantly reduced by NAC. Although NAC pretreatment significantly alleviated LPS-induced hepatic GSH depletion, DL-buthionine-(SR)-sulfoximine, an inhibitor of GSH synthesis, did not influence the protective effect of NAC on GalN/LPS-induced apoptotic liver injury. Conclusion: NAC attenuates GalN/LPS-induced apoptotic liver injury via its strong ROS scavenging and anti-apoptotic effects.